Canadian Broadcasting Policy, Capitalism, and CanCon: Balancing Economic and Cultural Objectives with the Online Streaming Act - Cooling, Christine Rose (Canadian Journal for the Academic Mind, 2024)
In April of 2023, Bill C-11, the Online Streaming Act, was given Royal Assent to amend Canada’s 1991 Broadcasting Act to regulate transnational, American-based online streaming services that lack intrinsic reason to enhance and foster conceptions of a distinctive ‘Canadian identity.’ Under this contentious new scope of broadcasting legislation, alongside radio and television, Internet streaming services are now required to, among other things, make maximum or predominant use of Canadian creative resources in the creation, production, and distribution of programming or otherwise contribute to those Canadian resources in an equitable manner, as well as support the production and distribution of original Canadian content (CanCon) in both official languages. From a critical political economic perspective, this introductory paper explores how Bill C-11 is a legislative measure aimed at countering the economic and cultural hegemony of online streaming giants, which predominantly disseminate American and other global content. As set forth in Section 3(1) of the 1991 Broadcasting Act, the Canadian broadcasting system should safeguard, enrich, and strengthen the cultural, political, social, and economic fabric of the nation; however, cultural objectives cannot be met without first achieving economic objectives. This paper argues that the Online Streaming Act seeks to safeguard Canada’s cultural industries by ensuring that CanCon is prioritized and protected against the encroachments of a relentless capitalist market driven by transnational corporations, which necessitates a delicate balancing of economic and cultural objectives.